Preliminary analysis of early and late radiation responses in 3D image-guided brachytherapy for cervical cancer - Olga B. Andreyeva; Tasbolat A. Adylkhanov; Dilyara R. Kaidarova; Isa G. Isayev; Tolegen S. Kurmangaliyev; Zaituna A. Khismetova; Natalya E. Glushkova (Russian Open Medical Journal)
Rationale – The use of 3D image-guided brachytherapy (3D-IGBT) allows adequately optimizing the dose distribution to bring a target therapeutic dose to clinical target volume (CTV), thereby minimizing an impact on critical organs, while ensuring a decrease in the incidence and severity of radiation-caused complications. Use of 3D-IGBT also allows improving the quality of life in patients with cervical cancer. Objective – To conduct a preliminary analysis of the incidence of early and late radiation responses in 3D-IGBT of locally advanced cervical cancer (LACC). Materials and Methods – The objects of our study were female patients with stages IIB and IIIB of cervical squamous cell carcinoma, without confirmed metastases, preceding chemotherapy (CHT) and/or radiation therapy (RT), and surgical interventions in this localization, who underwent combined chemoradiotherapy during the study. Results – Statistically significant results were obtained when analyzing the incidence of late radiation responses. It is important to point out that when assessing early toxicity in the main group with 3D-IGBT, grade 3 responses were not diagnosed, while in the control group, they were observed in 4 (9.1%) women. For instance, the manifestation of grade 3 delayed radiation injuries in the rectum was diagnosed in 3 (6.8%) women in the control group, while in the main group, they were not detected. Grade 2 cystitis was observed in a smaller number of women in the group with 3D-IGBT, compared with the control group (9.1% vs. 13.6%, p<0.05). Grade 3 delayed radiation responses in the bladder were diagnosed in 4 (9.1%) women in the control group, whereas among the patients of the main group with 3D-IGBT, they were not recorded at all (p <0.05). Grade II reactions in the vaginal mucosa and cervix were diagnosed more often in the control group (16.7% vs. 13.6%, p<0.05). Conclusion – Hence, the method we have used to optimize the treatment of LACC by means of 3D planning in accordance with toxicity criteria exhibited a definite advantage, compared with RT with 2D planning. Based on the results of our research, we concluded that optimization of RT for LACC using 3D-IGBT created clinically favorable conditions for effective therapy: it reduced the risk of displacement of the applicators and decreased an impact on the patient via reducing the total radiation doses and incidence of severe early and late toxic effects, providing good outcomes of local control regardless of tumor size and clinical stage.